Improved performance of ZnO/polymer hybrid photovoltaic devices by combining metal oxide doping and interfacial modification - Pachoumi, Olympia; Bakulin, Artem A.; Sadhanala, Aditya; Sirringhaus, Henning; Friend, Richard H.; Vaynzof, Yana (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Photoinduced charge separation at hybrid organic-inorganic interfaces is poorly understood and challenging to control. We investigate charge separation at a model system of ZnO/poly(3-hexylthiophene) (P3HT) and employ Sr doping of ZnO and phenyl-C61-butyric acid (PCBA) self-assembled modification to study and enhance the charge separation efficiency. We find that doping alone lowers the efficiency of charge separation due to the introduction of defect states at the oxide surface. However, with the combination of doping and molecular modification, charge separation efficiency is significantly enhanced due to the passivation of interfacial traps and improved modifier coverage. This demonstrates a complex noncumulative effect of doping and surface modification and shows that with the correct choice of metal oxide dopant and organic modifier, a poorly performing hybrid interface can be turned into an efficient one.